2014
DOI: 10.1128/iai.01922-14
|View full text |Cite
|
Sign up to set email alerts
|

Placental Cytokine and Chemokine Profiles Reflect Pregnancy Outcomes in Women Exposed to Plasmodium falciparum Infection

Abstract: g Pregnancy-associated malaria (PAM) can lead to severe complications for both mother and baby. Certain placental cytokine/ chemokine profiles have been shown to reflect poor pregnancy outcomes, including maternal anemia and low birth weight. In intervillous plasma samples from 400 Beninese women living in an area where Plasmodium falciparum is endemic, we quantified 16 cytokines/chemokines. We assessed their profiles in groups with PAM, with maternal anemia, with preterm births, or with a low birth weight for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 33 publications
8
35
2
1
Order By: Relevance
“…This was more marked in the primipara. These observations corroborate previous findings in Africa where high plasma levels of IL-10 were associated with malaria infection during pregnancy (Kabyemela et al, 2008;Nmorsi et al, 2010;Boström et al, 2012;Chandrasiri Upeksha et al, 2013;Chêne et al, 2014). High IL-10 levels have also been reported in mice models during pregnancy malaria (Megnekou et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…This was more marked in the primipara. These observations corroborate previous findings in Africa where high plasma levels of IL-10 were associated with malaria infection during pregnancy (Kabyemela et al, 2008;Nmorsi et al, 2010;Boström et al, 2012;Chandrasiri Upeksha et al, 2013;Chêne et al, 2014). High IL-10 levels have also been reported in mice models during pregnancy malaria (Megnekou et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…While a previous study demonstrated an association between cord blood cytokine levels of IFN-γ, IL-1β, TNF-α, IL-12p70, IL-10 cytokines, and reduced birth weight [33], this study, for the first time, shows that levels of IL-28A, IL-27 and IL-17E are elevated in cord plasma rather than in maternal peripheral plasma, and correlate positively with increasing baby birth weight. This positive association between birth weight and both the Th1-promoting (IL-27, IL-28A) and Th2-promoting cytokines (IL-17E) is consistent with the findings of Chêne and colleagues, who reported an association between low birth weight and decreasing level of both IFN-γ and IL-5 in intervellous plasma samples from Beninese women [34]. Findings from this study indicate that IL-28A, IL-27 and IL-17E cytokines might be implicated in fetal growth and suggest that a better understanding of the fetal environment mediated by multiple cytokines may be important for optimizing fetal growth outcomes in many settings.…”
Section: Discussionsupporting
confidence: 91%
“…Several previous studies have shown elevated levels of type 2 anti-in ammatory cytokines IL-10 and IL-4 in the malariainfected group [13,15,23,25,30,31]. Our ndings were different from those reported by Bayoumi et al [11] and Chêne and et al [12] who found higher levels of IL-4 and IL-10 in the non-infected group. The ndings of the increased IL-6 levels in non-infected women is in agreement with the results of other studies [11,16,32,33].…”
Section: Discussioncontrasting
confidence: 99%
“…P. falciparum infection during pregnancy increases the placental levels of IL-10 and IL-4 [13,25]. Elevated levels of the placental plasma anti-in ammatory cytokine, IL-10, were associated with PM, and were implicated in the pathogenesis of severe anemia [9,12,13]. Moreover, IL-10 has been identi ed as an immunosuppressive cytokine associated with poor pregnancy outcome in a mouse model of PM [26].…”
Section: Introductionmentioning
confidence: 99%